Evolution and comparison of the expression of TCP genes in the benincaseae and cucurbiteae tribes - Shuoshuo Wang; Wenli Li; Han Jin (Scientific Reports)
Abstract TCP genes are plant-specific transcription factors that play essential roles in plant growth, development, metabolism, and responses to biotic and abiotic stresses. However, the roles of TCP genes in Cucurbitaceae species remain unknown. In this study, 111 and 119 TCP genes were identified in the Benincaseae (C. melo, C. sativus, C. lanatus and L. siceraria) and Cucurbiteae (C. maxima, C. moschata and C. pepo) tribes, respectively, and were analyzed. Segmental duplication, tandem duplication, and whole-genome duplication (WGD) were identified as the major driving factors in the expansion of TCP genes in Cucurbitaceae species, with the majority of TCP genes undergoing purifying selection. Using the melon genome as a reference, an integrated map containing 29 loci across nine chromosomes was constructed, 28 of which were shared by seven Cucurbitaceae species. Gene structure analysis revealed that their function was conserved. The result of promoter sequence analysis indicated that TCP genes have many phytohormone-related cis-regulatory elements. GO term enrichment analysis showed that TCP genes were the major regulators of many downstream transcriptional networks and primarily functioned in the nucleus. Transcriptome analysis of different tissues and developmental stages of the Cucurbiteae tribe revealed tissue-specific spatial and temporal expression patterns of TCP genes, suggesting that TCP genes play an important role in the growth and development of Cucurbitaceae. Gene expression profiling demonstrated that TCP genes are involved in the responses of plants to abiotic and biotic stresses. In conclusion, this is the first systematic analysis of TCP genes in Cucurbitaceae, which provides deeper insights into their evolutionary dynamics and functional properties, which may be crucial for the genetic improvement of Cucurbitaceae.